Standardization in measurement: philosophical, historical and sociological issues - Schlaudt, Oliver; Huber, Lara (Pickering & Chatto Publishers, 2015)
The application of standard measurement is a cornerstone of modern science. In this collection of essays, standardization of procedure, units of measurement and the epistemology of standardization are addressed by specialists from sociology, history and the philosophy of science
Description based upon print version of record
Keywords: Electronic books; Geschichte; Metrologie; Standardisierung; Maßeinheit; Messung